Unraveling the microbiome–aroma Nexus: a metagenomic and volatile compound analysis of Yunnan cigars - Pan, Jing; Huang, Ming-Da; Wang, Jin; Zhao, Jian-Xiong; Yang, Bin; Yang, Hong-Hui; Huang, Jin-Sheng; Su, Yu-Long; Song, Xue-Ru; Wang, Wei-Guang; Bu, Ling-Duo (Frontiers in Microbiology, 2025)
IntroductionUnderstanding how microbial communities influence aroma profiles is critical to improving cigar quality. However, comparative studies examining the microbiome–aroma nexus across major cigar-producing regions remain limited.MethodsWe integrated high-throughput metagenomic sequencing with volatile organic compound (VOC) profiling to investigate microbial community structure and aroma compounds in four Yunnan cigars and two Cuban cigars.ResultsBacillus spp. was consistently dominant across all samples, while Yunnan cigars exhibited higher microbial diversity. A total of 121 VOCs were detected, with nicotine, ylangene, δ-elemene, (R,S)-anatabine, and phenethyl alcohol identified as key aroma components. Nicotine, accounting for 29.7–55.0% of total VOC content, was positively correlated with Enterobacter and Escherichia, and negatively with Corynebacterium and Brachybacterium. Ylangene showed strong positive associations with Brachybacterium and Yaniella. After FDR correction, 26 differential VOCs were identified across cigar groups. KEGG pathway analysis revealed functional enrichment in carbohydrate, amino acid, and lipid metabolism. Principal component analysis indicated that the aroma complexity of certain Yunnan cigars, particularly YX4, approached that of Cuban cigars.DiscussionOur findings demonstrate that region-specific fermentation microbiota are intricately linked to the production of key VOCs. This work provides a scientific framework for optimizing cigar fermentation through microbial regulation and supports the potential for targeted microbial inoculation to enhance sensory quality and global competitiveness.